Purification of soluble guanylate cyclase from rat liver - Braughler, J. Mark (1979)
Soluble guanylate cyclase [GTP pyrophosphate-lyase (cyclizing), EC 4.6.1.2] has been purified from rat liver and exhibited a single protein band on polyacrylamide gels coincident with activity and indicative of a molecular weight of 150,000. The apparent specific activity of the purified enzyme was 276 nmol of cyclic GMP formed per mg per min with Mn(2+) as the cation cofactor and 23.8 nmol of cyclic GMP formed per mg per min with Mg(2+). This represented 9200-fold and 7400-fold purifications of Mn(2+) and Mg(2+) activities, respectively. The specific activity of soluble guanylate cyclase was not constant with protein concentration. At all stages of purification, increasing the enzyme concentration in the guanylate cyclase assay increased the apparent specific activity of the preparation. The purified enzyme could be activated by nitroprusside, nitric oxide, arachidonate, linoleate, oleate, and superoxide dismutase. However, the degree of activation was dependent upon the concentration of enzyme protein assayed.